APLIKASI BEBERAPA KONSENTRASI AIR KELAPA TERHADAP PERTUMBUHAN TUNAS CABANG PULAI GADING (Alstonia scholaris (L.)R. BR.) - Wasgian Sri Hendrawi; M. Mardhiansyah; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Procurement of medicinal plants is an urgent issue and the demand for increased community use traditional medicine. One the herbs that has not been developed is Alstonia scholaris. Propagation is conventionally the success rate still low. Vegetative propagation can be done using branch shoots, can be stimulated by growth regulators naturally one them is coconut water. This research aims to determine the effect of coconut water as plant growth regulator and the optimal concentration on the growth shoots branch Alstonia scholaris. This research uses aRandomized Complete Design (RCD) consisting of 6 treatments with 4 replications and some degree concentration of coconut water.K0: concentration 0% coconut water, K1: concentration 20% coconut water, K2: The concentration 40% coconut water, K3: concentration 60% coconut water, K4: coconut water concentration 80% and K5: 100% coconut water concentration.The results showed K3 (coconut water concentration of 60%) is the optimal treatment to stimulate the growth of branches Alstonia scholaris in aquadesmedia to sprout for 13,41 days,the number of branches shoot 4,00 and branch shoot long 8,73 mm. Keywords: Branch shootAlstonia scholaris (L.) R. BR., coconut water, aquades.